B. K. S, IYENGAR YOGA : THE PATH TO HOLISTIC HEALTH - Iyengar, B. K. S., 1918-2014; Bradley, Nick (London : Dorling Kindersley Limited, 2021)
An accessible illustrated guide to Iyengar yoga from globally recognized yoga authority B.K.S. Iyengar. Discover the benefits of yoga for the mind, body, and spirit with this definitive guide from world-renowned yoga authority B.K.S. Iyengar. Learn how you can use yoga to improve every aspect of your life with B.K.S. Iyengar, globally respected for his holistic approach and technical accuracy. In B.K.S. Iyengar Yoga- The Path to Holistic Health, the guru himself guides you through more than 50 yoga poses, each with step-by-step instructions illustrated in full colour. Iyengar even explains his philosophy throughout the book - it's like having yoga classes with him as your own personal instructor. A special, 20-week beginners' yoga course makes yoga accessible for people of all ages and abilities. Twenty classic Iyengar yoga poses have a unique, 360-degree presentation so that you can see the correct position from all angles.
" The definitive step-by-step guide " --cover.
Keywords: Hatha yoga; Mind and body; Health